The Effect of Concentration Levels Neurospora sp and Times in Fermentation of Palm Oil on Contents of Dry Matter, Crude Protein, and Crude Fiberaw - Hasmida, Hasmida; Hasanuddin, Asriani; Syahrir, Syahrir; Aidah, Nur (AgriSains, 2021)
The purpose of this study was to determine the effect of the interaction between the concentration and time of the Neurospora sp. fungus on palm oil fermentation on the dry matter, crude protein and crude fiber content. This study used a completely randomized design (CRD) with a 3x3 factorial pattern, each treatment was repeated 2 times. The first factor was the concentration level of the fungus (0%, 5%, 10%) and the second factor was the fermentation time (48, 72, and 96 hours). The results of the analysis of variance showed that the interaction treatment between the concentration level of Neurospora sp. And the fermentation time of oil palm sludge had a very significant effect (P <0.01) on the dry matter and crude protein content, while the crude fiber content had no significant effect (P> 0.05). ). Independently, the concentration level and time significantly affected the dry matter content, crude protein and crude fiber. The highest value of dry matter was obtained at a combination of 72 hours and a concentration of 10% (W3K10% = 66.323%) and for crude protein, namely 96 hours and a concentration of 10% (W3K10% = 21.430%), while in crude fiber there was a decrease in each time or concentration.